Craniofacial Autonomic Dysfunction in Migraine: Implications for Treatment and Prognosis. Issue 1 (March 2020) - Cortez, Melissa M.; Millsap, Leah; Brennan, K. C.; Campbell, Corey L.
Abstract : Background: Craniofacial autonomic signs and symptoms (CASS) are relatively underrecognized in the evaluation of migraine headache. Yet, these features provide insight into diagnostic criterion, therapeutic approaches, and overarching disease burden. Evidence Acquisition: This review aims to summarize relevant literature evaluating autonomic dysfunction, with focus on CASS, in migraine through targeted literature searches in PubMed. Full articles of original data published between 1974 and 2019 were identified using MeSH terms with no search limits. Results: Although CASS are typically clinically evaluated by subjective patient report, investigational measures of cranial autonomic function have identified marked distinctions between headache attack and attack-free intervals. The presence of CASS during an attack does not differ based on age, sex, or presence of aura. Unilateral CASS may be predictive of longer, more frequent, and/or severe attacks and often co-occur with sensory dysfunction such as allodynia and photophobia. Although limited research has been performed to evaluate targeted therapeutics for migraine with CASS, triptans and onabotulinumtoxinA may demonstrate greater effects in this group. Conclusions: Migraine remains a debilitating disorder with significant community-wide impacts, necessitating continued evaluation of contributing features. Consideration of CASS provides important insight into potential treatment approaches and the effectiveness of novel therapeutic interventions aimed at improving overall disease burden. However, further investigation is needed to fully understand primary craniofacial features in migraine, and how these might inform individualized treatment decisions.